Hematopoietic-extrinsic cues dictate circadian redistribution of mature and immature hematopoietic cells in blood and spleen - Stenzinger, Miriam; Karpova, Darja; Unterrainer, Christian; Harenkamp, Sabine; Wiercinska, Eliza; Hoerster, Keven; Pfeffer, Martina; Maronde, Erik; Bönig, Halvard (Cells, 2019)
Circadian oscillations in circulating leukocyte subsets including immature hematopoietic cells have been appreciated; the origin and nature of these alterations remain elusive. Our analysis of wild-type C57BL/6 mice under constant darkness confirmed circadian fluctuations of circulating leukocytes and clonogenic cells in blood and spleen but not bone marrow. Clock gene deficient Bmal1−/− mice lacked this regulation. Cell cycle analyses in the different hematopoietic compartments excluded circadian changes in total cell numbers, rather favoring shifting hematopoietic cell redistribution as the underlying mechanism. Transplant chimeras demonstrate that circadian rhythms within the stroma mediate the oscillations independently of hematopoietic-intrinsic cues. We provide evidence of circadian CXCL12 regulation via clock genes in vitro and were able to confirm CXCL12 oscillation in bone marrow and blood in vivo. Our studies further implicate cortisol as the conveyor of circadian input to bone marrow stroma and mediator of the circadian leukocyte oscillation. In summary, we establish hematopoietic-extrinsic cues as causal for circadian redistribution of circulating mature/immature blood cells.